Resistance and compliance in women's academic identity work in the Global South. (10th April 2019) - Haeruddin, M. Ikhwan Maulana; Pick, David; Thein, Htwe Htwe
Abstract: The aim of this study is to explore women academic's identity work in the context of the Global South (Indonesia). This is done by examining how the interplay between macro‐level social, cultural and political influences and micro‐processes produce moments of compliance and resistance. To this end, the following research question is posed: What is the nature of identity work among women academics in higher education institutions of the Global South where there are shifting and conflicting social and cultural conditions? This study contributes by illuminating the ways in which women comply with or resist traditional and contemporary organisational and occupational structures that produce gender inequality. It also contributes to understanding how the interplay of power and resistance influences women's academic identity work in developing nations.